Hysterothylacium Persicum (Nematoda: Raphidascarididae) Parasite of Orangespotted Grouper Epinephelus coioides (Forsskål, 1775) Iraqi Marine Water Fishes - Bannai, Majid Abdul Azizi (Iraqi Journal of Science, 2018)
Hysterothylacium is one of the most important nematode parasites parasitizing fish, and it’s the most diverse species nematodes of marine parasites, these species attach to the intestinal wall via their mouth lips adaptation. In the present study, seven out of 56 fish specimens (12.5 %) were found to be infected by the adult worms of Greasy grouper fishes Orangespotted grouper Epinephelus coioides (Forsskål, 1775)from locations of marine coastal water, Arabian Gulf, Iraq. A new recorded of Hysterothylacium spp. collected are morphologically described, genetically and Sccaning Electron Microscope (SEM) images for new systematic observations, on dorsal labium, sub ventral labia, posterior end of a the female and the male. Based on the study of the gene sequencer data and SEM images, it will be suggested that species are H. persicum. The study provides us some data on the taxonomy of these parasites in the Arabian Gulf. The gross examination of the fish’s intestine food items and the Relationships of fish length, In this study showing that the length ranges for adult infected were 25-45 cm long, and the major food items found in the stomach were a Largest group of miscellaneous of fishes length more than 25 cm , whereas crustaceans miscellaneous parts of animal body, i.e. appendages, chela, parts of the carapace of crustaceans were found in stomachs in all the month including except some of them in stomach of length less than 20 cm , it was clear that the 25-45cm ctotal length feed mainly on fish that explain fishes are the second intermediate host of IV larval stage of nematodes. In the present reported can consider that the Epinephelus coioides as a new host for Hysterothylacium persicum and a newly recorded in Iraqi marine water . The aim of the current study is to diagnose and study new species of parasites that belong to the genus throughout the morphological studies along with the image data selected for SEM and sequence and combined with the other species of Hysterothylacium that reside in the Iraqi marine water and the relationships of fish length, food items and parasite infection.